Urgency of Soft-Skill Development in Vocational Education for Children with Special Needs - Aini, Sylvi Noor; Susetyo, Budi; Novianti, Ranti; Diniarti, Gena; Nadiyah, Salma (Department of Special Education, 2023)
This study aims to describe the relationship of striving for superiority as a soft skill to learning motivation. The approach used is a quantitative approach with descriptive methods in deaf students with a sample of Cerebral Palsy students in Bandung Regency. Correlative testing is performed using spearman correlation tests between striving for superiority variables and learning motivation variables. The results showed that striving for superiority has a very strong correlation to learning motivation so that it becomes an aspect that must be developed in vocational education as part of soft skills. Striving for superiority can help learners deal with various circumstances or problems through self-concept and coping strategies that are factors that influence striving for superiority. Self-concept and coping strategy will strengthen interpersonal and intrapersonal learners with special needs in undergoing the vocational development process as a form of post-school career preparation.